Kalanchoe tubiflora extract inhibits cell proliferation by affecting the mitotic apparatus - Hsieh Yi-Jen; Yang Ming-Yeh; Leu Yann-Lii; Chen Chinpiao; Wan Chin-Fung; Chang Meng-Ya; Chang Chih-Jui (BMC, 2012)
Abstract Background Kalanchoe tubiflora (KT) is a succulent plant native to Madagascar, and is commonly used as a medicinal agent in Southern Brazil. The underlying mechanisms of tumor suppression are largely unexplored. Methods Cell viability and wound-healing were analyzed by MTT assay and scratch assay respectively. Cell cycle profiles were analyzed by FACS. Mitotic defects were analyzed by indirect immunofluoresence images. Results An n-Butanol-soluble fraction of KT (KT-NB) was able to inhibit cell proliferation. After a 48 h treatment with 6.75 μg/ml of KT, the cell viability was less than 50% of controls, and was further reduced to less than 10% at higher concentrations. KT-NB also induced an accumulation of cells in the G2/M phase of the cell cycle as well as an increased level of cells in the subG1 phase. Instead of disrupting the microtubule network of interphase cells, KT-NB reduced cell viability by inducing multipolar spindles and defects in chromosome alignment. KT-NB inhibits cell proliferation and reduces cell viability by two mechanisms that are exclusively involved with cell division: first by inducing multipolarity; second by disrupting chromosome alignment during metaphase. Conclusion KT-NB reduced cell viability by exclusively affecting formation of the proper structure of the mitotic apparatus. This is the main idea of the new generation of anti-mitotic agents. All together, KT-NB has sufficient potential to warrant further investigation as a potential new anticancer agent candidate.